The Influence of Mutations and Career Development on Employee Performance with Variables of Work Spirit as a Mediation Variable in SMPN 193 - Adinugraha, Hildan; Suharto; Silitonga, Eddy Sanusi (Madani Connection, 2025)
This research aims to: 1) Analyze the effect of mutation on employee performance, 2) Analyze the influence of Career Development on Employee Performance. 3) analyze the influence of Work Morale on Employee Performance 4) How does Mutası and career development influence Performance with the mediating variable Work Morale of SMPN 193 teachers. This research was conducted on employee teachers at Pertana Negeri 193 Middle School, East Jakarta Administrative City. The sample in this study was 49 people. The sampling technique uses random analysis techniques with analysis methods using descriptive analysis methods and path analysis. The results of this research show that : 1) there is an influence of mutation on employee performance. 2) there is an influence of career development promotion on employee performance. 3) there is an influence of Work Morale on Employee Performance. 4) There is an influence of mutation and career development on performance with the mediating variable work enthusiasm